Financial Sector Assessment : Bulgaria - World Bank (Washington, DC, 2013)
This Financial Sector Assessment (FSA) summarizes the Financial Sector Assessment Program (FSAP) findings for Bulgaria, and reports on the actions of the government and the Bulgarian National Bank (BNB) to date in response to the FSAP recommendations. The FSAP mission visited Sofia during the period October 29 to November 14, 2001. The Bulgaria FSAP took place after five years of aggressive financial reforms in response to the deep economic and financial crisis of 1996-97. After the collapse of the banking system and establishment of the Currency Board Arrangement (CBA) in July 1997, the government and the BNB pursued structural and institutional reforms in both the enterprise and banking sectors, including the privatization of about 85 percent of the banking system assets, mainly to foreign financial institutions, and the upgrading of banking supervision capabilities at the BNB. The FSAP mission occurred at a time when the banking system had stabilized, but financial intermediation remained low compared to the more advanced transition economies. In addition to the assessments of compliance with standards and codes, the Bulgaria mission focused on addressing the constraints to lending and advising the BNB on how to ensure that an expansion of bank lending does not jeopardize the gains in financial stabilization. The FSAP findings were major inputs to the medium term program to be supported by the Programmatic Adjustment Loans (PALS).